Adaption of the ex vivo mycobacterial growth inhibition assay for use with murine lung cells - Painter, H; Prabowo, SA; Cia, F; Stockdale, L; Tanner, R; Willcocks, S; Reljic, R; Fletcher, HA; Zelmer, A (Springer Nature, 2020)
In the absence of a correlate(s) of protection against human tuberculosis and a validated animal model of the disease, tools to facilitate vaccine development must be identified. We present an optimised ex vivo mycobacterial growth inhibition assay (MGIA) to assess the ability of host cells within the lung to inhibit mycobacterial growth, including Bacille Calmette-Guérin (BCG) and Mycobacterium tuberculosis (MTB) Erdman. Growth of BCG was reduced by 0.39, 0.96 and 0.73 log10 CFU following subcutaneous (s.c.) BCG, intranasal (i.n.) BCG, or BCG s.c. + mucosal boost, respectively, versus naïve mice. Comparatively, a 0.49 (s.c.), 0.60 (i.n.) and 0.81 (s.c. + mucosal boost) log10 reduction in MTB CFU was found. A BCG growth inhibitor, 2-thiophenecarboxylic acid hydrazide (TCH), was used to prevent quantification of residual BCG from i.n. immunisation and allow accurate MTB quantification. Using TCH, a further 0.58 log10 reduction in MTB CFU was revealed in the i.n. group. In combination with existing methods, the ex vivo lung MGIA may represent an important tool for analysis of vaccine efficacy and the immune mechanisms associated with vaccination in the organ primarily affected by MTB disease.